Glutamate decarboxylase-1 is essential for efficient acclimation of Arabidopsis thaliana to nutritional phosphorus deprivation - Benidickson, Kirsten H (The New phytologist, 2023)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.